Multi-center study on overall clinical complexity of patients with prolonged disorders of consciousness of different etiologies - Estraneo, A; Masotta, O; Bartolo, M; Pistoia, F; Perin, C; Marino, S; Lucca, L; Pingue, V; Casanova, E; Romoli, A; Gentile, S; Formisano, R; et al. (Brain injury, 2021)
Aim: to assess overall clinical complexity of patients with acquired disorders of consciousness (DoC) in vegetative state/unresponsive wakefulness syndrome (VS/UWS) vs. minimally conscious state- MCS) and in different etiologies.. Design: Multi-center cross-sectional observational study. Setting: 23 intensive neurorehabilitation units. Subjects: 264 patients with DoC in the post-acute phase: VS/UWS = 141, and MCS = 123 due to vascular (n = 125), traumatic (n = 83) or anoxic (n = 56) brain injury. Main Measures: Coma Recovery Scale-Revised, and Disability Rating Scale (DRS); presence of medical devices (e.g., for eating or breathing); occurrence and severity of medical complications. Results: patients in DoC, and particularly those in VS/UWS, showed severe overall clinical complexity. Anoxic patients had higher overall clinical complexity, lower level of responsiveness/consciousness, higher functional disability, and higher needs of medical devices. Vascular patients had worse premorbid clinical comorbidities. The two etiologies showed a comparable rate of MC, higher than that observed in traumatic etiology. Conclusion: overall clinical complexity is significantly higher in VS/UWS than in MCS, and in non-traumatic vs. traumatic etiology. These findings could explain the worse clinical evolution reported in anoxic and vascular etiologies and in VS/UWS patients and contribute to plan patient-tailored care and rehabilitation programmes.